(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Solomon is the twentieth and youngest son of David. According to most Islamic traditions in 1003 BC, God assigned him as the following prophet after David, while the Bible only presents him as a mighty monarch. The present research aims to investigate the interpretations of the tale of Prophet Solomon (PBUH) in the Surahs Al-Anbiya and Naml. The present study is descriptive-analytical. In this research, by using library studies, such as the study of prominent mystical books and interpretations of the Qur’an - including Tafsir al-Tabari, Tafsir-e Gazur, Taj al-Tarajim, Tafsīr Abū al- Futūḥ, Majma‘ al-Bayan fi-Tafsir al-Qur’an, Surābādi’s Commentary, Kashf al-Asrar - and forming indices from the interpretations of the Qur’an and striking mystical sources of the prose texts belonging up to the end of the ninth century and the classification of the indices, the topics were analyzed. The results revealed that in the account of "Head Head", monotheism was taught, and polytheism was warned. In the story of "Asif ibn Barkhiya", hadith narrators have declared that he called to the great name and earth was compressed. Then he took the queen’s throne and brought it to Solomon. Analysts with philosophical tendencies maintain that God overthrew the throne of the Queen of Sheba in the land of Sheba and, in the presence of Solomon, reassembled it. Also, in describing the story "Bilqis - the Queen of Sheba", the courage of reformability and making the right choice in life dilemmas are taught.